Suicide ideators and attempters : differences and risk factors for the use of violent methods at admission in a psychiatric ward - Vacas, Sara Malta (2019)
Copyrights belong to the Author(s). Suicidology Online (SOL) is a peer-reviewed open-access journal publishing under the Creative Commons Licence 3.0.